Odpowiedzi

2010-03-13T23:03:59+01:00
2NaOH +H2SO4=Na2SO4 +2H2O
m H2SO4= 2*1g+32g +4*16g=98g
m NaOH=2 *(23g +16g +1g)=80g
80g NaOH--------------98g H2SO4
x g NAOH---------------20g H2SO4
x=80g *20g/98g
x=16,5g
odp: do zobojętnienia 20 g H2SO4 potrzeba ok 16,5 g NaOH.
2010-03-13T23:13:18+01:00
H₂SO₄ + 2NaOH → Na₂SO₄ + 2H₂O

m H₂SO₄ = 2*1g+1*32g+4*16g = 2g+32g+64g = 98g
m NaOH = 2(23g+16g+1g) = 2*40g = 80g

98g ------------------ 80g
20g ------------------ x g

98x = 80*20
98x = 1600 |:98
x ≈ 16,3g